The experience of the Hitler Youth - boys in the national-socialism - Figiel, Dominik (Journal of Education Culture and Society, 2020)
Losing the First World War, unemployment, the generation gap and the cult of youth led to the party of Adolf Hitler gaining popularity in the Weimar Republic. Using slogans of the restoration of a strong Germany the national socialists organized structures, which formed and educated German Youth. Hitler Youth – brought up according to the rule: “youth leads youth” – was a very fertile environment for the spread of the idea of national-socialism. The specific values – racial supremacy, honour, obedience – handed down by parents were the beginning of the Nazi indoctrination. In the later period such organizations as Bund Deutscher Madel or Hitlerjugend took power over German youth. Education, upbringing, ideological content used by the institutions in Nazi Germany are described in the extensive literature on the subject. However, very important are the experiences of individual members of the Hitler Youth that show the Nazi youth activities from a time perspective. Experiences such as the wisdom of life, and gained knowledge, enable recognition and description of the reality which is discussed. The scope of historical and pedagogical research shows the essential facts constituting the full picture of the life of young people during Nazi era.